Control–cooperation interfaces in global strategic alliances: a situational typology and strategic responses - Luo, Yadong; Shenkar, Oded; Gurnani, Haresh (Journal of International Business Studies, 2008)
This article applies the dialectical logic of loose coupling to interpartner exchanges in order to analyze the dynamics of global strategic alliances. We develop a typology of control and cooperation that defines alliance states or situations according to their level of cooperation under private and collective control. In the private control–cooperation interplay, contending, honeymoon, and coopetition situations arise, depending on the levels of private control and cooperation. In the collective control–cooperation interplay, the loosely connected, the equity hostage, the tightly integrated, and the trusting states emerge according to the levels of collective control and cooperation. We illustrate how an individual partner strategically responds to the control–cooperation interplay under each situation or state, and develop hypotheses explicating how these strategic responses are influenced by relational characteristics such as goal congruity, resource complementarity, and bargaining asymmetry between foreign and local partners.